A new TPE-based foam material from EPDM/PPB blends, as a potential buffer energy-absorbing material - Z. X. Zhang; Y. M. Wang; Y. Zhao; X. Zhang; A. D. Phule (eXPRESS Polymer Letters, 2021)
Blends from the thermoplastic elastomer (TPE) of Propylene/1-butene copolymers (PPB) and Ethylene–propylene–diene monomer (EPDM) were successfully prepared by melt-mixed in an internal mixer and crosslinking through highenergy electron beam irradiation technology. The foaming process was achieved with the assistance of eco-friendly supercritical carbon dioxide (sc-CO2). The effect of EPDM content on foaming, morphology, thermal, and mechanical properties of EPDM/PPB blends with varied irradiation dose were investigated. Microstructural analysis revealed a perfect compatibility of PPB and EPDM in TPE. The increased EPDM content caused a decrease in the mechanical properties (hardness and tensile strength) of TPE; however, it has been improved with the increased irradiation dose. The thermal analysis indicated that the addition of EPDM and high-energy electron beam crosslinking resulted in a new melting peak near 150 °C in TPE, and a new crystalline phase appears during the crystallization process. Repeated processing performance tests showed that the incorporation of higher PPB content reduces the loss of mechanical properties of the prepared blend. The micro-morphology of the cell structure in foamed TPE material was investigated, and it was found that the size of cell structure gradually decreased with the increased EPDM content; however, the cell size has a tendency to increase first and then decrease with the increase of irradiation dose. At 40 kGy irradiation dose, the cell structure size is the largest among all EPDM/PPB foams. The cyclic compression test of the TPE foamed material showed that the material’s resistance to repeated compression got promoted with the increased EPDM content.